Constructing Halal Identity in Global Markets: A Critical Discourse Analysis of Halal Branding Practices - Syahadah Albaqiyatul Karimah; Nuruddin (Mozaic : Islam Nusantara, 2026)
This study examines how language constructs and communicates halal identity in global markets through an analysis of halal branding practices. While prior research has focused on certification, regulation, and consumer trust, limited attention has been given to the linguistic strategies shaping halal identity across cultural contexts. Employing a qualitative design and Critical Discourse Analysis (CDA), this study analyzes a corpus of 45 halal branding texts, including product labels, promotional slogans, and digital marketing content from Indonesia, Malaysia, and selected global brands. The findings reveal three dominant discursive strategies: (1) religious lexicalization (e.g., halal, tayyib, sharia-compliant), (2) hybrid identity framing that integrates Islamic values with global branding narratives, and (3) persuasive sloganization linking ethical consumption with lifestyle aspirations. The study also highlights cross-cultural tensions, where the universalization of halal values encounters challenges in local adaptation. This research contributes to sociolinguistics, marketing discourse, and halal studies by demonstrating the central role of language in constructing symbolic meanings of halal in the global economy. Practically, the findings offer insights for marketers and policymakers in designing culturally sensitive and linguistically effective halal branding strategies.